Emotional Loneliness in Elderly: Association with Cognitive Performance and Sleep Quality in One of Indonesia’s Rural Areas - Olga Atsira; Ayu Nisa'; Muhammad Hanun Mahyuddin; Rakha Rahmatullah; Aita Silia; Azimatul Karimah (Jurnal Psikiatri Surabaya, 2024)
Introduction: A growing body of studies focuses on the association between loneliness defined as social isolation with sleep quality and cognitive performance, whereas emotional loneliness has not received much attention. Objective: Determine the association between emotional loneliness, cognitive performance, and sleep quality in one of Indonesia’s rural areas. Method: The sample comprised 30 Indonesian individuals > 60 years old living in rural areas. Cognitive performance was evaluated using the Mini-Mental State Examination (MMSE). The quality of sleep was measured using the Pittsburgh Sleep Quality Index. Meanwhile, emotional loneliness was conducted using the UCLA Loneliness Scare. Using Pearson correlation, bivariate analysis was performed between physical health, sociodemographic factors, cognitive function, and sleep quality with loneliness. Results: There is a significant moderate correlation between loneliness and diabetes (p-value = 0.001, r = 0.573). There is a significant low correlation between loneliness and MMSE score (p-value = 0.03, r = 0.397). And there is a significant high correlation between loneliness and PSQI score (p-value = 0.000, r = 0.886). Two components of sleep quality that show a statistically significant correlation with loneliness are subjective sleep quality (p-value = 0.000, r = 0.6) and sleep duration (p-value = 0.023, r = 0.414 ). Conclusion: This is the first study to examine the association between emotional loneliness with sleep quality and cognitive function in one of Indonesia’s rural areas. Keywords: Loneliness, Sleep quality, Cognitive performance, Elderly